2017
DOI: 10.7251/comen1702121p
|View full text |Cite
|
Sign up to set email alerts
|

Current Distribution Dependence on Electric Field in Helically Coiled Carbon Nanotubes

Abstract: Experimentally is confirmed that helically coiled carbon nanotube (HCCNT) could be used as a small solenoid for generating spatially localized magnetic field. Current distribution during diffusive electronic transport likewise the inductivity of this quantum conductor depends on electric field. Despite slightly lower electron mobility in HCCNTs than that of the straight single wall carbon nanotubes, the coiled nanotubes are attractive for application as nonlinear nano-solenoids. Nonequilibrium electron distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We hope that these results pave the way for a more realistic design of the nanosolenoids. To the best of our knowledge, this is the first study of the finite-length nanosolenoid where the fringe effects were not ignored. It is shown that the magnetic fields of the finite nanosolenoids can be an order of magnitude smaller than the field of infinite ones, and spatial distribution of fields is more complex.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…We hope that these results pave the way for a more realistic design of the nanosolenoids. To the best of our knowledge, this is the first study of the finite-length nanosolenoid where the fringe effects were not ignored. It is shown that the magnetic fields of the finite nanosolenoids can be an order of magnitude smaller than the field of infinite ones, and spatial distribution of fields is more complex.…”
Section: Introductionmentioning
confidence: 94%
“…2 As examples of pure carbon-based materials, one can also cite the nanometer-sized graphite helical structures, which behave as a collection of individual, closely packed nanosolenoids, 4 some graphene spiral structures, 5 and the various helically coiled nanotubes with very complex structures. 6,7 The large magnetic fields are anticipated to be realized using solenoids with the carbon nanotubes-copper composite materials. 8 Finally, our previous calculations show that much more efficient nanosolenoids are possible if one turns from carbon to the chiral gold nanotubes (AuNTs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation